Developing a Worksheet Based on Problem-Based Learning for Mathematics Subjects in Grade V Elementary Schools - Kurino, Yeni Dwi; Haryanti, Yuyun Dwi; Yonanda, Devi Afriyuni; Kania, Nia; Rismawati, Silvyra (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractMathematics learning in elementary schools still faces challenges related to the limited availability of instructional materials that support active learning and students’ problem-solving skills. Student worksheets commonly used in classrooms tend to be conventional and have not fully integrated problem-based learning approaches, which limits students' engagement and ability to apply mathematical concepts in real-world situations. Therefore, this study aimed to develop a problem-based learning student worksheet for mathematics learning on three-dimensional shapes in third-grade elementary school and to examine its quality. This study employed a research and development approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were students from one third-grade elementary school class. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The data were analyzed using descriptive quantitative and qualitative techniques. The results indicated that the developed Worksheet were valid based on expert judgments, practical according to positive responses from teachers and students, and effective, as indicated by the improvement in students’ learning outcomes after using the worksheets. The results of the study indicate that the developed worksheet has a very high level of validity (4.39), very practical usability (89.83%), and is effective in improving students’ learning outcomes, as indicated by the increase in the average score from 63.20 to 81.35. Thus, the problem-based learning Worksheet is suitable for use as instructional material to support meaningful mathematics learning in elementary schools.Keywords: student’s worksheet, problem based learning, ADDIE, three-dimensional shapes, elementary mathematics.AbstrakPembelajaran matematika di sekolah dasar masih menghadapi tantangan terkait dengan keterbatasan ketersediaan bahan ajar yang mendukung pembelajaran aktif dan kemampuan pemecahan masalah siswa. Lembar kerja siswa yang umum digunakan di kelas cenderung konvensional dan belum sepenuhnya mengintegrasikan pendekatan pembelajaran berbasis masalah, yang membatasi keterlibatan siswa dan kemampuan untuk menerapkan konsep matematika dalam situasi dunia nyata. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan lembar kerja siswa berbasis masalah untuk pembelajaran matematika tentang bangun tiga dimensi di kelas tiga sekolah dasar dan untuk menguji kualitasnya. Penelitian ini menggunakan pendekatan penelitian dan pengembangan dengan model ADDIE, yang terdiri dari tahapan Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Subjek penelitian adalah siswa dari satu kelas tiga sekolah dasar. Data dikumpulkan melalui lembar validasi ahli, kuesioner tanggapan guru dan siswa, dan tes hasil belajar. Data dianalisis menggunakan teknik kuantitatif dan kualitatif deskriptif. Hasil menunjukkan bahwa lembar kerja yang dikembangkan valid berdasarkan penilaian ahli, praktis menurut tanggapan positif dari guru dan siswa, dan efektif, sebagaimana ditunjukkan oleh peningkatan hasil belajar siswa setelah menggunakan lembar kerja tersebut. Hasil penelitian menunjukkan bahwa lembar kerja yang dikembangkan memiliki tingkat validitas yang sangat tinggi (4,39), kegunaan praktis yang sangat tinggi (89,83%), dan efektif dalam meningkatkan hasil belajar siswa, sebagaimana ditunjukkan oleh peningkatan nilai rata-rata dari 63,20 menjadi 81,35. Dengan demikian, Lembar Kerja Pembelajaran Berbasis Masalah cocok digunakan sebagai bahan pembelajaran untuk mendukung pembelajaran matematika yang bermakna di sekolah dasar.Kata kunci: LKPD, pembelajaran berbasis masalah, model ADDIE, bangun ruang, matematika sekolah dasar.